The Application Progress of Patient-Derived Tumor Xenograft Models After Cholangiocarcinoma Surgeries - Wu, Jun; Sheng, Jiyao; Qin, Hanjiao; Cui, Mengying; Yang, Yongsheng; Zhang, Xuewen (Frontiers in Oncology, 2021)
Surgical treatment is the only possible cure for cholangiocarcinoma (CCA) at present. However, the high recurrence rate of postoperative CCA leads to a very poor prognosis for patients, effective postoperative chemotherapy is hence the key to preventing the recurrence of CCA. The sensitivity of CCA to cytotoxic chemotherapy drugs and targeted drugs varies from person to person, and therefore, the screening of sensitive drugs has become an important topic after CCA surgeries. Patient-Derived tumor Xenograft models can stably retain the genetic and pathological characteristics of primary tumors, and better simulate the tumor microenvironment of CCA. The model is also of great significance in screening therapeutic targeted drugs after CCA, analyzing predictive biomarkers, and improving signal pathways in prognosis and the basic research. This paper will review the current establishment methods and applications of the patient-derived tumor xenograft model of cholangiocarcinoma, aiming to provide new ideas for the basic research and individualized treatment of cholangiocarcinoma after surgery.